Externalizing personality characteristics define clinically relevant subgroups of alcohol use disorder. - Ildikó Kovács (PLoS ONE, 2022)
Aims Higher levels of externalizing characteristics, i.e. impulsivity, novelty seeking and aggression, could contribute to the development, progression and severity of alcohol use disorder (AUD). The present study aims to explore whether these externalizing characteristics together have a potential group-forming role in AUD using latent profile analysis (LPA). Methods Externalizing characteristics of 102 AUD patients were analyzed using LPA to explore the group-forming role of externalizing symptoms; groups were compared in terms of demographic and alcohol-related variables, indices of psychopathological, depressive and anxiety symptom severity. Results LPA revealed and supported a two-group model based on externalizing symptoms. The group with higher levels of externalizing symptoms showed significantly elevated levels of alcohol-related and anxio-depressive symptoms. Conclusions Externalizing characteristics converge and have a group-forming role in chronic AUD, and are associated with a more severe form of AUD. By making the diagnostic category less heterogeneous, these different subtypes within AUD may provide aid in tailoring treatments to patients' specific needs.